Biochemical Markers for Differential Diagnosis of Stroke: A Biochemical Markers Study of S100B Protein, Neuron Spesific Enolase (NSE), Myelin Basic Protein (MBP), and Heart-Type Fatty Acid Binding Protein (H-FABP) - Evy Liswati; Andi Wijaya; Teguh A. S. Ranakusuma (The Prodia Education and Research Institute (PERI), 2009)
BACKGROUND: Differential diagnosis between hemorrhagic and ischemic stroke, which determine how to treat the patients, was performed by CT-Scan. CT-Scan is not always available in all Indonesian health care facility. Other alternative using biochemical markers needed to be studied.METHODS: In total of 44 stroke patients consist of 25 ischemic and 19 hemorrhagic strokes according to CTScan, participated in this study. S100B Protein, NSE, MBP and H-FABP concentration in the blood of each stroke patient was determined.RESULTS: Among the biochemical markers used, only MBP at cut off point 0,712 ng/ml could be used for diagnosing hemorrhagic from ischemic stroke for serum samples obtained until 72 hours after onset of the stroke. If samples could be obtained within 24 hours, S100B Protein and MBP could be used for diagnosing hemorrhagic from ischemic stroke. If both markers increased (S100B Protein >7.55 pg/ml and MBP >0.109 ng/ml) sensitivity and specificity would be 77.8% and 84.6% respectively.CONCLUSIONS: MBP and S100B Protein are promising markers for differential diagnosis of hemorrhagic from ischemic stroke. Using serum samples obtained within 24 hours after onset and multiple markers (MBP and S100B Protein) will improved diagnostic performance of the test.KEYWORDS: Stroke, S100B Protein, Neuron Specific Enolase, Myelin Basic Protein, and Heart-Type Fatty Acid Binding Protein